Comprehensive Analysis of Secondary Metabolites in the Extracts from Different Lily Bulbs and Their Antioxidant Ability - Yu-Chao Tang; Yi-Jie Liu; Guo-Ren He; Yu-Wei Cao; Meng-Meng Bi; Meng Song; Pan-Pan Yang; Lei-Feng Xu; Jun Ming (MDPI AG, 2021)
The genus Lilium contains more than 100 wild species and numerous hybrid varieties. Some species of them have been used as medicine and food since ancient times. However, the research on the active components and the medical properties of lilies has only focused on a few species. In this study, the total phenolic acid content (TPC), total flavonoid content (TFC), and antioxidant capacity of 22 representative lilies were systematically investigated. The results showed that the TPC, TFC and antioxidant activity were highly variable among different lilies, but they were significantly positively correlated. Hierarchical cluster analysis indicated that L. henryi and L. regale were arranged in one group characterized by the highest TPC, TFC and antioxidant capacity, followed by Oriental hybrids and Trumpet and Oriental hybrids. The traditional edible and medicinal lilies were clustered in low TPC, TFC and antioxidant capacity group. A total of 577 secondary metabolites, including 201 flavonoids, 153 phenolic acids, were identified in the five species with great differences in antioxidant capacity by extensive targeted metabonomics. Differentially accumulated metabolites (DAMs) analysis reviewed that the DAMs were mainly enriched in secondary metabolic pathways such as isoflavonoid, folate, flavonoid, flavone, flavonol, phenylpropanoid, isoquinoline alkaloid biosynthesis, nicotinate and nicotinamide metabolism and so on. Correlation analysis identified that 64 metabolites were significantly positively correlated with antioxidant capacity (r ≥ 0.9 and p < 0.0001). These results suggested that the genus Lilium has great biodiversity in bioactive components. The data obtained greatly expand our knowledge of the bioactive constituents of Lilium spp. Additionally, it also highlights the potential application of Lilium plants as antioxidants, functional ingredients, cosmetic products and nutraceuticals.